Parliamentary Rights Scrutiny and Counter-Terrorism Lawmaking in Australia - Sarah Moulds (Jember University Press, 2019)
This paper evaluates the impact of pre and post-enactment scrutiny of Australia’s counter-terrorism laws enacted from 2001 until 2018. Parliamentary scrutiny of rights-engaging laws is particularly critical in the Australian content, as Australia relies on a parliamentary model of rights protection at the federal level. The evaluation framework employed in this Paper considers a range of evidence to provide a holistic account of the impact of legislative scrutiny on the content, development and implementation of Australia’s counter-terrorism laws. This includes consideration of the legislative impact of scrutiny on the content of the law, the role scrutiny plays in the public and parliamentary debate on the law, as well as the hidden impact scrutiny, may be having on policy development and legislative drafting. The results are surprising. This study finds that parliamentary rights scrutiny, particularly by parliamentary committees, has had a rights-enhancing (although rarely rights-remedying) impact on the counter-terrorism laws. Further, this research finds that the hidden or behind-the-scenes impact of parliamentary scrutiny provides a particularly fertile ground for improving the rights-protecting capacity of the Australian legislative scrutiny system. These findings and the evaluation framework employed in this Paper have application and benefits for other jurisdictions seeking to understand and improve the quality of their legislative scrutiny regimes.